2014
DOI: 10.1371/journal.pone.0090907
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Mediates Sustained Inactivation of Breast Cancer-Associated Myofibroblasts via Up-Regulation of Tumor Suppressor Genes

Abstract: BackgroundActive cancer-associated fibroblasts (CAFs) or myofibroblasts play important roles not only in the development and progression of breast carcinomas, but also in their prognosis and treatment. Therefore, targeting these cells through suppressing their supportive procarcinogenic paracrine effects is mandatory for improving the current therapies that are mainly targeting tumor cells. To this end, we investigated the effect of the natural and pharmacologically safe molecule, caffeine, on CAF cells and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 46 publications
3
24
0
2
Order By: Relevance
“…We have recently shown that caffeine mediates sustained inactivation of breast cancer-associated myofibroblasts [15]. Therefore, we sought to investigate whether this sustained effect is mediated through the inhibition of the IL-6/STAT3/NF-κB loop.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently shown that caffeine mediates sustained inactivation of breast cancer-associated myofibroblasts [15]. Therefore, we sought to investigate whether this sustained effect is mediated through the inhibition of the IL-6/STAT3/NF-κB loop.…”
Section: Resultsmentioning
confidence: 99%
“…The mRNA level of AUF1, another target of STAT3, was also persistently reduced in response to caffeine (Figure 6B). This clearly shows that caffeine blocks the IL-6/STAT3/NF-κB positive feedback loop, which explains its observed sustained effect on active breast stromal fibroblasts [15]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations